The Impact of Genetic Factors on the Development of Type 2 Diabetes and Possible Pathways for its Correction - Sembayeva, Zhibek; Ilderbayev, Oralbek; Tazhibayeva, Damira; Zhanilova, Ainur; Ilderbayeva, Aruzhan (Acta medica Lituanica, 2026)
Aim: The aim of this study was to investigate the impact of genetic factors on the development of type 2 diabetes in the population of Kazakhstan. Materials and methods: The methodology included the collection of demographic data, the analysis of biochemical parameters, and the application of polymerase chain reaction genotyping for single-nucleotide polymorphisms in genes associated with type 2 diabetes. Result: The main results of the study demonstrated that patients with type 2 diabetes had a 20% higher body mass index (29.5±4.2 kg/m2 versus 24.3±3.1 kg/m2) and 29% lower physical activity (3.2±1.5 hours per week versus 4.5±2.0 hours per week) compared with the control group. Biochemical parameters showed a 50% higher glucose level (7.8±2.1 mmol/L versus 5.2 ± 0.8 mmol/L), insulin levels by 76% (15.3±5.2 microunits per millilitre versus 8.7±2.5 microunits per millilitre), and glycated haemoglobin by 42% (7.5±1.2% versus 5.3±0.5%) in patients with type 2 diabetes. The genetic analysis revealed substantial associations between type 2 diabetes and risk alleles in the TCF7L2 (rs7903146), KCNJ11 (rs5219), FTO (rs9939609), PPARG (rs1801282), and ADIPOQ (rs1501299) genes, which were linked to compromised insulin secretion and metabolic anomalies in the study population. Conclusions: The practical significance of the study lies in the potential application of these findings to develop personalised approaches for the prevention and treatment of type 2 diabetes, including lifestyle modification, the use of modern pharmaceuticals, and anti-inflammatory drugs to improve glucose control in patients.